2021
DOI: 10.3390/jcdd8020008
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Models of Cancer Therapy-Induced Cardiovascular Toxicity

Abstract: Purpose of review: Both traditional and novel cancer therapies can cause cardiovascular toxicity in patients. In vivo models integrating both cardiovascular and cancer phenotypes allow for the study of on- and off-target mechanisms of toxicity arising from these agents. The zebrafish is the optimal whole organism model to screen for cardiotoxicity in a high throughput manner, while simultaneously assessing the role of cardiotoxicity pathways on the cancer therapy’s antitumor effect. Here we highlight establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Transparent zebrafish larvae are also widely used for the assessment of drug-induced cardiotoxicity 45 . This kind of toxicity is one of the most frequent reasons for drug withdrawals 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Transparent zebrafish larvae are also widely used for the assessment of drug-induced cardiotoxicity 45 . This kind of toxicity is one of the most frequent reasons for drug withdrawals 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, zebrafish cardiomyocytes express voltage-gated sodium channels, Ltype and T-type calcium channels and potassium channel, similarly to vertebrates (67). These electrophysiological characteristics of zebrafish model are useful to study drugassociated QT prologation (68). Furthremore, with the advances in genome editing technology, transgenic zebrafish models were developed.…”
Section: Preclinical Animal Modelsmentioning
confidence: 99%
“…Moreover, a study that used a genetically modified mouse model to identify the molecular basis of radiation-induced cardiotoxicity demonstrated that p53 functions in endothelial cells to prevent radiation-induced myocardial injury in mice (72). In another study, in which female rats received a 24 Gy localized whole-heart radiation, myocardial strain worsened post-RT, especially at 10-weeks and in lateral regions (68). Combined radiation therapy and antineoplastic drugs have been little studied through animal models.…”
Section: Preclinical Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its amenability to high-throughput genetic and compound screening, zebrafish (Danio rerio) has emerged as a highly prolific vertebrate animal model to study human cardiac diseases [7][8][9]. Surprisingly, many cardiac electrophysiological behaviors of zebrafish have higher conservation than mouse with humans [7].…”
Section: Introductionmentioning
confidence: 99%